Association of immune cell traits with Parkinson’s disease: a Mendelian randomization study - Song, Zhiwei; Li, Wangyu; Han, Yupeng; Xu, Yiya; Ding, Haiqi; Wang, Yinzhou (Frontiers in Aging Neuroscience, 2024)
Background Immunity and neuroinflammation play crucial roles in the pathogenesis of Parkinson’s disease (PD). Nonetheless, prior investigations into the correlation between immune inflammation and PD have produced varying results. Identifying specific immune cell phenotypes that are truly associated with PD is challenging, and the causal relationship between immune cells and PD remains elusive. Methods This study conducted a comprehensive two-sample Mendelian randomization (MR) analysis, employing five distinct analytical approaches, to clarify the causal connection between immune cell characteristics and the risk of PD. Utilizing GWAS data, we investigated the causal relationship between 731 immune cell traits and PD. These immune cell phenotypes encompass absolute cell (AC) counts, median fluorescence intensity (MFI), and relative cell (RC) counts for B cells, cDCs, mature stage T cells, monocytes, myeloid cells, TBNK (T cells, B cells, and natural killer cells), and Tregs, as well as the logistic parameter (MP) for cDCs and TBNK. Results The inverse variance weighted (IVW) analysis indicated that Myeloid DCs (p = 0.004), HVEM expression on CD45RA− CD4+ T cells (p = 0.007), CD62L− CD86+ Myeloid DCs (p = 0.015), and HLA DR expression on monocytes (p = 0.019) were associated with a reduced risk of PD. CD14+ CD16+ monocytes (p = 0.005), HLA DR+ NK cells within CD3− lymphocytes (p = 0.023), and CD28 expression on activated & secreting Tregs (p = 0.032) were associated with an increased risk of PD. Conclusion This study establishes a causal link between immune cell phenotype and the pathogenesis of PD, identifying several specific immune cell characteristics associated with PD. This could inspire researchers to delve into the pathogenesis of PD at the cellular subtype level, and aid in the identification of potential pharmacological protein targets for PD.